2014
DOI: 10.1111/ijd.12585
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of methotrexate plus pioglitazone vs. methotrexate alone in the management of patients with plaque‐type psoriasis: a single‐blinded randomized controlled trial

Abstract: Recently, thiazolidinediones have shown to be efficacious with a favorable safety profile when used in the treatment of chronic plaque-type psoriasis. The aim of this study was to evaluate and compare the efficacy and safety of a combination of methotrexate plus pioglitazone and methotrexate alone in plaque-type psoriasis. A total of 44 adult patients with plaque-type psoriasis were included in the study. Patients were randomized to treatment with methotrexate alone (group A) or methotrexate plus pioglitazone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(56 reference statements)
0
39
0
1
Order By: Relevance
“…It was observed that troglitazone normalized the histological features of psoriatic skin and reduced the hyperplasia in mouse and human skin models of psoriasis. Pioglitazone is also noted to enhance the effect of methotrexate in plaque psoriasis in a recent study [47]. However, topical administration of these agents has failed to demonstrate any significant response in pilot studies among patients with psoriasis [46].…”
Section: Psoriasismentioning
confidence: 99%
“…It was observed that troglitazone normalized the histological features of psoriatic skin and reduced the hyperplasia in mouse and human skin models of psoriasis. Pioglitazone is also noted to enhance the effect of methotrexate in plaque psoriasis in a recent study [47]. However, topical administration of these agents has failed to demonstrate any significant response in pilot studies among patients with psoriasis [46].…”
Section: Psoriasismentioning
confidence: 99%
“…A 2016 meta‐analysis of the efficacy of methotrexate in psoriasis showed that only 11 studies, which included randomized controlled trials (RCT), with a total number of 937 patients, were eligible to meta‐analyse . Most of the studies included in that meta‐analysis investigated the comparative efficacy of methotrexate versus other treatments, and most reported short‐term (12–16 weeks) efficacy of methotrexate . Meta‐analysis revealed that 45.2% of patients receiving methotrexate achieved a 75% reduction in Psoriasis Area and Severity Index (PASI) score during the week 12–16 treatment window .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of adverse effect was less as compared to a previous study. 21 Our study had two important advantages. It had a longer duration in comparison with previous studies considering the effect of pioglitazone on plaque-type psoriasis.…”
Section: Resultsmentioning
confidence: 99%